2012
DOI: 10.1016/j.exer.2011.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Cellular distribution of the IGF-1R in corneal epithelial cells

Abstract: This study characterized the expression and subcellular localization of the IGF-1R in human corneal epithelial cells. Using a human telomerase-immortalized corneal epithelial cell line, IGF-1R expression and localization was assayed by immunofluorescence and subcellular fractionation followed by western blot. IGF-1R expression was confirmed in primary cultured human corneal epithelial cells. Nuclear localization was assessed under basal and IGF-1 stimulated culture conditions; phosphorylation status of the rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
23
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 39 publications
9
23
1
Order By: Relevance
“…Indeed, the translocation of Igf-1 into the nuclei has been reported in regenerating human muscle satellite cells, in which Igf-1 protein was detected in the nuclei at 24 hours after the start of regeneration, and then was diffusely expressed in the myofibers after 72 hours (McKay et al, 2008). Other studies have indicated that the Igf-1 receptor (IGF1R) can localize to the nucleus in corneal epithelial cells (Robertson et al, 2012) and in renal and breast cancer cells (Aleksic et al, 2010). Recently, it been shown that nuclear IFG1R functions as a transcriptional co-activator of LEF1/TCF, leading to increases in protein levels of LEF1 target genes (Warsito et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the translocation of Igf-1 into the nuclei has been reported in regenerating human muscle satellite cells, in which Igf-1 protein was detected in the nuclei at 24 hours after the start of regeneration, and then was diffusely expressed in the myofibers after 72 hours (McKay et al, 2008). Other studies have indicated that the Igf-1 receptor (IGF1R) can localize to the nucleus in corneal epithelial cells (Robertson et al, 2012) and in renal and breast cancer cells (Aleksic et al, 2010). Recently, it been shown that nuclear IFG1R functions as a transcriptional co-activator of LEF1/TCF, leading to increases in protein levels of LEF1 target genes (Warsito et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The binding affi nity for IGF-1 in corneal epithelial cells was 4 n m and the presence of specifi c receptors for IGF-1 was shown. In another study, subcellular expression, distribution and localization of IGF-1 receptor in human corneal epithelial cells was demonstated (Figure 4.5a, b) [115]. Simultaneous expression of 135-kDa α -subunits and 95-kDa β -subunits within the nuclear compartment was identifi ed, indicating the presence of full receptor.…”
Section: Growth Factor Receptormentioning
confidence: 95%
“…Negative control (NC, bottom row), primary antibody omitted. Scale: 22.5 μ m. Reproduced with permission of [115]. However, at later stages of lens development, TGFB family members have been shown to induce pathological changes in lens epithelial cells.…”
Section: Transforming Growth Factor-β Receptormentioning
confidence: 98%
See 2 more Smart Citations